Development of Fluorescent Assay for Monitoring of Dehalogenase Activity. Issue 3 (28th August 2018) - Nevolova, Sarka; Manaskova, Elisabet; Mazurenko, Stanislav; Damborsky, Jiri; Prokop, Zbynek
Abstract : The rapid accumulation of sequence data and powerful protein engineering techniques providing large mutant libraries have greatly heightened interest in efficient methods for biochemical characterization of proteins. Herein is reported a continuous assay for screening of enzymatic activity. The assay is developed and tested with the model enzymes haloalkane dehalogenases and relies upon a fluorescent change of a derivative of 8‐hydroxypyrene‐1, 3, 6‐trisulphonic acid due to the pH drop associated with the dehalogenation reactions. The assay is performed in a microplate format using a purified enzyme, cell‐free extract or intact cells, making the analysis quick and simple. The method exhibits high sensitivity with a limit of detection of 0.06 mM. The assay is successfully validated with gas chromatography and then applied for screening of 12 haloalkane dehalogenases with the environmental pollutant bis(2‐chloroethyl) ether and chemical warfare agent sulfur mustard. Six enzymes exhibited detectable activity with both substrates. The within‐day variability of the assay for five replicates ( n  = 5) was 21%. Abstract : A novel fluorescent assay for detection of haloalkane dehalogenase enzymatic activity has been developed. The assay is based on the modified pH indicator of 8‐hydroxypyrene‐1, 3, 6‐trisulphonic acid. Activity measurement is performed in a 96‐well microplate format using purified enzymes, cell‐free extracts or intact cells, making the analysis simple, quick and sensitive. The developed assay can be used for identification and biochemical characterization of novel haloalkane dehalogenases and for high‐throughput screening of enzymes improved by protein engineering. The assay is generally applicable with a wide range of enzymes that cause the formation or consumption of protons during their catalytic cycle.